Sustainable development of rural areas - Methodological issues - Werner Hediger; Annemarie Dorenbos; Bernard Lehmann (European Regional Science Association (ERSA), 1998)
Sustainable development is both a global and local challenge to managing change. It requires integrating social, ecological and economic objectives and system requirements that are generally expressed in terms of maintaining some suitably defined aggregates of social, ecological and economic capital. Apart from global environmental constraints, these aggregates are mainly determined at the local scale. This is of particular importance for the development of rural areas that more directly depend on environmental resources than urban economies, and that are characterised by a semi-natural to natural landscape which provides amenity and recreational values to the urban and rural population. Yet, the threat to rural areas is that they are under pressure of urbanisation. This goes along with land use change and socio-cultural change, and thus with alterations of the regional ecological and social capital. This results in trade-offs between short-term goals of development and long-term goals of sustainability. On the one hand, the development of rural areas depends on available resources, current institutions and technologies, and the competitiveness of local goods and services. On the other hand, sustainability calls for maintaining the regional capital stock (local economic, social and ecological assets) over time. An integrated approach is required to address these trade-offs. To this end, we provide a transdisciplinary synthesis of research on rural development, and present a concept for improving rural development strategies toward achieving long-term goals of sustainability. Apparently, sustainable development is the key concept for integrating the above issues. It does not need each asset to be conserved. Rather, sustainable development requires that conservation and change are balanced through an adaptive process of optimisation across the various system goals. This implies a development path which is constrained by the boundaries of the regional opportunity space for sustainable development. These boundaries are characterised by general system requirements, such as compliance with critical levels of natural and social capital, economic stability, satisfaction of basic needs, equity within and between generations, and efficient use of scarce resources. They are not constant, but vary in space and time. As an adequate method of research on sustainable development in rural areas, and to provide assistance to local actors and the political process, we propose a combination of formal analyses and participatory approaches. First, to assess the boundaries of the above opportunity space, within which sustainable development is feasible, a formal analysis is required. It must integrate scientific and local knowledge, cultural values, along with local and national goals of economic and social development. Second, to create new development potentials, the opportunity space must be expanded. This can be achieved through innovation and institutional change, which requires local initiative and capacity building amongst all actors involved. Finally, the local actors are the key players in implementing measures at their respective level of activity in order to manage change within the boundaries of the opportunity space of sustainable development.
Keywords: 330